(3GdcaGjIs - (3eMeO HGbQ GdSHRGhQjs ((3eMeO Hf eMeO WjH NhRGfjs)
(3ChdgG (B:s
... (3GdaUd GdKGfj aj GdZSd hajg CfXGQ ; GdChd GdCZSGd GdhGLHI ZSd GdLfGHI hGdMjV hGdfaGS hGdGSJMGVI eY ZeS GdbWfI hZSd GdCehGJ hZSd eS GdCehGJ ef GdfGS HYO HQOg HGdehJ hbHd GdZSd GdeTghQ hG YOG Pdc eSJMH , GdfXQ GdKGfj (B...s
(3BNQgG (B:s
.. (3ajQLY Ydi GdhQKI hdG jHYO JQLjM Gdbhd GdChd Ydi Gdbhd HGYJHGQ GdKdK hGdeTJQj HGdNjGQ Hjf GdELGRI hGdaSN dJHYjV GdUabI EPG de jcf YGdeG Hchfg eQjVG hef Mce GdeQjV eG PcQ hdG jLH Ydi cd efgeG HPd eGdg ddBNQ HGdYhV hGddg Gdehab(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B18\843s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis